Reflexões sobre a tributação do ganho de capital da pessoa física na operação de incorporação de ações frente ao conceito constitucional de renda - Albanezi, Thaís Blumer (2023)
This study intends to verify whether the merger of shares (incorporação de ações) generate capital gain subject to the taxation by individual income tax. For this analysis, we have analyzed the concept of income adopted by the Federal Constitution and by the National Tax Code. In our legal system, the Federal Constitution is responsible for defining a minimum semantic core of the concept of income, which is unraveled in the complementary legislation. As a result, we have reached the conclusion that the taxable income tax in our tax system corresponds to the equity increase that is effective, available and realized. Based on this, unrealized gains could not be characterized as income for tax purposes. Once analyzed the concept of income, we studied the institute of the merger of shares from a corporate standpoint and verified that the transaction implies in a “legal subrogation” for the partner of the company whose shares are merged. Analyzing the transaction under the concept of income constructed in the previous topics, we were finally able to analyze whether the transaction of merger of shares is subject to income tax and we concluded that it is not possible to identify, in the merger of shares, a taxable income. Our analysis allowed us to verify that the great controversies about the tax effects of the merger of shares is more connected to the concept of income adopted by tax specialists than to the effective nature of the transaction